Study on the sickle anchoring joint in external prestressing strengthening of portal frame. (December 2020) - Xin, Yajun; Wu, Junqi; Wu, Qingbo; Cui, Weilong; Zhang, Shilian; Cheng, Shuliang
Abstract: Due to the change in the use of function or the addition of new equipment, some problems have occurred in the used portal steel frames, including increased load and unsatisfactory bearing capacity. Therefore, the used portal steel frames need to be reinforced and improved. As a safe, reliable, economical, and convenient strengthening method, the external prestressing strengthening technology is often used to reinforce the portal frame. In this paper, in order to avoid damage to the original structure in the strengthening process due to welding, drilling and other connection methods, the sickle anchoring joint was applied in the external prestressing strengthening of portal frame. The principle of lever was used to fix sickle anchoring joint on the lower flange of the steel beam to achieve effective anchoring of the steel cable and steel beam. The FEM simulation was used to study the stress characteristics of the sickle anchoring joint, including equivalent stress, contact status, etc. In addition, in practice, the joint was used for the strengthening of portal frame. The strain at different parts of rigid frame and the deflection in mid-span were measured in the experiment. The experimental and simulation results were compared to verify the effectiveness of joint. The study showed that the sickle anchoring joint had the advantages of simple structure, clear force, high safety and effectiveness. Thus the sickle anchoring joint can be applied to the external prestressing strengthening of the portal frame.